The Implementation of Teacher Role Modeling in Aqidah Akhlak Learning at Islamic Junior High School - Ikhlasud Dafa; Ahmad Ma’ruf (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2026)
Background: Teacher role modeling is a fundamental approach in Islamic education because students tend to imitate the attitudes and behaviors demonstrated by teachers during the learning process. Based on Bandura’s social learning theory, moral values are effectively internalized through observation and imitation of positive role models. Objective: This study aims to analyze the implementation of teacher role modeling in Aqidah Akhlak learning at MTs Miftahul Khoir Karangrejo, including its forms, students’ responses, and the supporting and inhibiting factors. Method: This research employed a qualitative descriptive approach. Data were collected through classroom observations, semi-structured interviews with one Aqidah Akhlak teacher and eight students, and documentation of learning activities. Findings and Implications: The findings indicate that teacher role modeling was reflected in discipline, polite communication, responsibility, and respectful interaction. Students responded positively, showing improved moral understanding and learning motivation. However, exemplary practices had not been systematically integrated into lesson planning. Supporting factors included the teacher’s consistent personality and a conducive classroom environment, while limited instructional time and diverse student characteristics became major challenges. Conclusion: Teacher role modeling effectively supports students’ moral character development. Integrating exemplary practices into lesson planning and teacher professional development is recommended to strengthen character education in Islamic schools.